Stakeholder Management: A Universal Strategic Health Services Management Approach to Unlock a Profitable Return on Investment - Shiri, Simon (Prabandhan: Indian Journal of Management, 2015)
There have been sustained global policy and fiscal pressures for businesses, including health care services to demonstrate unique customer-oriented entrepreneurship capabilities in terms of marketing and innovativeness, influenced by the recent global financial crisis, leading to business closures, budgetary shortfalls, and constant operational challenges for survival. For several health care managers, this entails effectively managing the increasing influence of active and powerful stakeholders to achieve a competitive advantage in terms of productive and allocative efficiency over customer-driven results and innovativeness. A focus on value addition by itself is a precursor of effective stakeholder management, clinician leadership model, and a decentralized activity based management, which integrates customer values from basic and expected services to desired and unexpected services as well as combining product quality and high quality customer services needed to usher a competitive advantage to organizations through cost leadership or product differentiation. However, a stakeholder management tool that is universally applicable across all health care business entities is still work in progress. This paper debated upon relevant previous literature on stakeholder management as a central feature for customerdriven business practices, for implementation in form of a universal stakeholder management tool, in order to advance sound entrepreneurship capabilities that support dynamic high quality customer care-driven health care and innovation.